LEVERAGE RATIO ANALYSIS COMPARISON BEFORE AND AFTER FIXED ASSETS REVALUATION IN JAKARTA STOCK EXCHANGE IMPACT ON INVESTMENT DECISIONS STUDIES ON THE COMPANY'S MANUFACTURING IES WHICH WENT PUBLIC ON THE JAKARTA STOCK EXCHANGE - Ardansyah ARDANSYAH; Jant Kennedy Junior (International Conference On Law, Business and Governance (ICon-LBG), 2016)
Increased exchange rate of US dollar against the rupiah resulted in the value of liabilities owned firms in US Dollars to be increased. This condition can affect the confidence of creditors and investors on the company's ability to meet its financial obligations The ability company in fulfilling its financial obligations is closely related to the company's capital strength.Policy revaluation of fixed assets taken companies that go public are expected to show the picture of the company's capital strength is better and show the wealth more reasonable position. This research was conducted to measure and verify whether there is a significant difference between the leverage ratio before and after the revaluation of fixed assets represented, Debt-to-equity ratio, Long-term debt to equity ratio, debt ratio, and Shareholder'sequity to total assets ratio. This study was conducted on 5 companies go public the revaluation of fixed assets during the period December 31, 2012 until December 31, 2013.The test results with Comparative Analysis of Two Samples Independent and with a significant level (α): 0:05 prove to a significant difference between the leverage ratio before and after the revaluation of fixed assets represented, Debt-to-equity ratio, Long-term debt to equity ratio, debt ratio, and Shareholder'sequity to total assets ratio. This proves that there is not much different between the existing leverage ratio.